Effect of 20-Hydroxyecdysone on Molt Cycle of Juvenile Macrobrachium rosenbergii (de Man) - Sajitha. S; Kiran Dube; A. K. Reddy (Journal of Indian Fisheries Association, 2016)
In crustaceans moult cycle is controlled by moult hormones. A moult hormone 20-hydroxyecdysone was tested on juvenile Macrobrachium rosenbergii. In this study the juveniles of M. rosenbergii were administered intramuscularly with different doses of 20-hydroxyecdysone i.e. 0.05, 0.1, 0.2, 0.3 and 0.4 µg/g body weight, and two sets kept as base control (without injection) and experimental control (injected with 10% ethanol). These sets were named as EO, EO', E1, E2, E3, E4 and E5 for base control, experimental control, 0.05, 0.1, 0.2, 0.3 and 0.4 µg per g body weight respectively. The moulting frequency was increased with reduced intermoult period of 11 days at E4 and E5 as compared to EO, EO', E1, E2 and E3 where moulting frequency was 15, 21, 18, 17 and 14 days respectively. The highest growth rate of 0.7g was achieved at E1, followed by E3 (0.5g), EO (0.4g), E2 (0.4g), E4 (0.4g), E5 (0.3g) and E0' (0.2g) simultaneously. The growth rate was same at EO, E2 and E4. The results indicate that there is no correlation between the dose of hormone and the growth pattern. Lowest survival of 67% was recorded at higher doses of 0.3 and 0.4 µg per g body weight as against 100% at other treatments. This is also an indication, at higher doses, though moulting frequency is increased with reduced intermoult period, no positive impact was noticed either on growth or in survival.